Methodical approach to justification of possible amount of capital project debt financing oflocal authorities (World of finance, 2019)
Introduction. The economic independence of local government is associated with the availability of capital expenditures financing funds which are decisive factor in boosting regional development. However, Ukrainian realities indicate a limited amount of their own financial resources for local authorities which should be directed to capital financing. Under such conditions, the problem of research on alternative forms of financing, one of which is debt finance, is becoming increasingly clear and requiring a scientificjustification forthe limits of their use.Purpose. Studying the forms of capital project financing of local government and developing and substantiating methodical approach for determining the maximum amount of debt finance at local level.Results. The generalization ofthe existing forms ofcapital project financing oflocal development in Ukraine, criteria of their choice are summarized. The direct connection between the territory debt potential and its financial capacity is proved. The expediency is substantiated and the methodology of using optimization linear programming methods in determining borrowing limits of cities is provided.Conclusions. The proposed methodology for assessing the potential of borrowing of local authorities primarily depends on the cost of the capital project, as well as ensuring the sustainability of the financial condition of the local budget. The scientific and practical value of the constructed model is to improve the methodological approach to defining the threshold value of the amount of borrowed funds that cities can attract for a specific capital project, subject to maintaining a high level of financial and debt sustainability of the local budget.